“EDUCATION AS THE PRACTICE OF FREEDOM” TO ADDRESS EDUCATIONAL POVERTY IN SUB-SAHARA AFRICA - Lushombo, Léocadie (Asian Horizons, 2018)
Educational Poverty refers to significant differences in cognitive style or development, past school history, or social/emotional development that significantly impede a person’s ability to function in regular learning environments without supports or accommodations. 1 A significant number of both religious and lay women in Sub-Saharan African countries are affected by such a poverty, including the Democratic Republic of the Congo. One of the influential factors of such poverty is the oppressive traditional gender norms which guide behaviour in both Church and society. This paper explains the ways such norms obstruct women’s education. In dialogue with Catholic social teaching and Martha Nussbaum’s cognitive capability, it develops a critical theological reflection based on Paulo Freire’s insights on Education as the Practice of Freedom that it proposes as a way out.